Recent results of studies of magnetic field distribution and neutron scaling on PF-1000 and PF-3 facilities - Krauz, V.; Mitrofanov, K.; Scholz, M.; Kubes, P.; Myalton, V.; Paduch, M.; Karpinski, L.; Koidan, V.; Mokeev, A.; Vinogradov, V.; Vinogradova, Yu.; Zielinska, E. (Вопросы атомной науки и техники, 2013)
The recent results of studies of the magnetic field distribution and the neutron yield scaling in two largest plasma focus facilities, PF-3 and PF-1000 is done. The power-law dependence of the neutron yield on the current in the imploding plasma sheath has been demonstrated experimentally. For the first time the presence of the Вz magnetic field components is experimentally shown. In the compression stage, the axial component of the magnetic field reaches several kG that comprises ~10 % of the azimuthal component. The presence of the Bz field is a powerful argument in favor of the existence of closed magnetic configurations, which play an important role in the generating of neutrons. Представлены результаты последних исследований распределения магнитного поля и скейлинга нейтронного выхода на двух крупнейших плазмофокусных установках ПФ-3 и ПФ-1000. Экспериментально показана степенная зависимость нейтронного выхода от величины тока в сжимающейся плазменной оболочке. Впервые экспериментально показано наличие Вz-компоненты магнитного поля. В стадии сжатия величина аксиальной компоненты магнитного поля достигает нескольких килограмм-сил, что составляет ~ 10% от величины азимутальной компоненты. Наличие Bz-поля является весомым аргументом в пользу существования замкнутых магнитных конфигураций, играющих важную роль в механизме генерации нейтронов. Представлено результати останніх досліджень розподілу магнітного поля і скейлінга нейтронного вихoдy на двох найбільших плазмофокусних установках ПФ-3 та ПФ-1000. Експериментально показана ступенева залежність нейтронного виходу від величини струму в плазмовїй оболонці, що стикається. Вперше експериментально показано наявність Вz-компоненти магнітного поля. У стадії стиснення величина аксіальної компоненти магнітного поля досягає декількох кілограм-сил, що складає ~ 10 % від величини азимутальної компоненти. Наявність Вz-поля є вагомим аргументом на користь існування замкнутих магнітних конфігурацій, що мають неаби яку роль у механізмі генерації нейтронів.